Effectiveness of practical training sessions to students / Mohamad Jauhari Iskandar Mat Jaafar, Muhammad Syazwan Syafiq Badry and Aizat Fahmi Mohd Zainuddin - Mat Jaafar, Mohamad Jauhari Iskandar; Badry, Muhammad Syazwan Syafiq; Mohd Zainuddin, Aizat Fahmi (2010)
How effective is the practical training sessions to Diploma in Pharmacy UiTM students? For more than 10 years, Diploma of Pharmacy Students was sent to attend an industrial attachment for 11 months. As known this 11 months attachment was nothing but revising, practicing and repeating knowledge gain back in the previous 2 years of theory learning in the class. Were you one of the great newborn of these practical students too? No offense because it should be more valuable if the last 11 months continued by furthering the current lessons in the class and more topics can be covered rather than repeating what had been learned before (attending a year of training sessions). To find out why this (learning session) is very important and how effective is the training sessions to students; we had conducted a questionnaires survey research on both groups - students undergoing practical sessions and students that didn't yet. Out of 167 people of the population, 50 people from both groups were involved to answer the questionnaires paper survey in order to find out who got the higher in knowledge level and by doing that we can find out “Is practical training sessions are very effective to students or not?”.